Pre-lithiated silicon-carbon negative electrode material and preparation method and application thereof
By pre-depositing lithium metal particles and nanosilicon particles in pores of porous carbon, pre-lithiated silicon carbon negative electrode material was prepared, which solved the problem of low efficiency and severe volume changes in the first week of silicon carbon negative electrode material in lithium-ion batteries. , achieving higher electrochemical performance stability and cycle life.
Patent Information
- Application Number
- CN202311076396.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-24
- Publication Date
- 2025-02-25
AI Technical Summary
The silicon-carbon anode material has low efficiency in the first week of lithium-ion batteries, and the volume changes violently during the battery cycle, resulting in unstable battery performance.
Prelithiated silicon carbon negative electrode material is prepared by pre-depositing lithium metal particles in pores of porous carbon to form pre-lithiated porous carbon, and then nanosilicon particles are deposited in pores. This material can quickly replenish lithium ions during the cycle, improve the efficiency of the first circle of Coulomb, and enhance the stability of electrochemical properties by improving the uniformity of silicon deposition.
It improves the first-circle Coulomb efficiency of lithium-ion batteries, enhances the stability of electrochemical performance, reduces the volume expansion rate, and improves the cycle life of the battery.
Smart Images

Figure CN119517975A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a pre-lithiation silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] Carbon-based negative electrode materials have become the most commercially successful negative electrode materials for lithium-ion batteries due to their excellent conductivity, low cost and suitable lithium storage sites. However, problems such as low specific capacity and poor lithium insertion rate have made the development of new high-capacity negative electrode materials the focus of research at this stage.
[0003] The theoretical capacity of silicon anode is more than 10 times that of graphite anode material (372mAh / g), up to 4200mAh / g, and silicon is abundant in nature, so it has become the most promising new anode material to replace graphite anode material. Studies have shown that porous silicon-carbon anode materials can effectively improve the problems of poor conductivity and volume expansion during lithium-ion battery reactions, but for high-energy silicon anode materials, the continuous consumption and generation of SE I film during battery cycling will cause drastic volume changes and seriously reduce the battery's first charge efficiency.
[0004] Therefore, it is necessary to develop a pre-lithiation negative electrode material that can be mass-produced and applied, so as to solve the problem of low coulombic efficiency of silicon-carbon negative electrode materials in the first week. Summary of the invention
[0005] The embodiment of the present invention provides a pre-lithiated silicon-carbon negative electrode material and a preparation method and application thereof, wherein pre-lithiated porous carbon is obtained by pre-depositing lithium metal particles in the pores of the porous carbon, and then depositing silicon particles in the pores, wherein the porous carbon has high strength and high hardness, and can effectively improve the volume expansion of silicon-containing particles during the charging and discharging process; and pre-lithiating the porous carbon in advance can, on the one hand, enable the material to quickly replenish lithium ions during the cycle process and improve the first-cycle coulomb efficiency of the material; on the other hand, compared with the situation where lithium and silicon are deposited at the same time, pre-lithiating first can increase the uniformity of silicon deposition, thereby making the electrochemical properties of the material more stable.
[0006] In a first aspect, an embodiment of the present invention provides a pre-lithiation silicon-carbon negative electrode material, the pre-lithiation silicon-carbon negative electrode material comprising: a composite particle, and a surface coating layer coated on the outer surface of the composite particle;
[0007] The mass of the composite particles accounts for 85%-99% of the total mass of the pre-lithiation silicon-carbon negative electrode material;
[0008] The composite particles are composites of pre-lithiated porous carbon and nano-silicon particles; the composite particles are obtained by uniformly depositing nano-silicon particles in the pores of the pre-lithiated porous carbon; the mass of the pre-lithiated porous carbon accounts for 15%-95% of the total mass of the composite particles;
[0009] The pre-lithiation porous carbon comprises lithium metal particles and porous carbon, wherein the lithium metal particles are attached to the surface of the pores of the porous carbon; the mass of the lithium metal particles accounts for 0.1%-10% of the total mass of the pre-lithiation silicon-carbon negative electrode material.
[0010] Preferably, the mass of the surface coating layer accounts for 1%-15% of the total mass of the pre-lithiation silicon-carbon negative electrode material;
[0011] The mass of the nano silicon particles accounts for 5%-75% of the total mass of the pre-lithiation silicon-carbon negative electrode material.
[0012] Preferably, the particle size D of the pre-lithiation silicon-carbon negative electrode material is 50 The diameter of the porous carbon pores is between 1nm and 80μm; the pore size of the porous carbon pores is between 0.1nm and 300nm; the porosity of the porous carbon is between 30% and 95%.
[0013] In a second aspect, an embodiment of the present invention provides a method for preparing the pre-lithiation silicon-carbon negative electrode material described in the first aspect, the preparation method comprising:
[0014] The lithium-containing compound and the porous carbon are fully mixed to obtain a mixed material, and then the mixed material is placed in a high-temperature furnace for heat treatment under a protective atmosphere to vaporize the mixed material, and after deposition, a pre-lithiated porous carbon with lithium metal particles attached to the pore surface of the porous carbon is obtained;
[0015] In a protective atmosphere, a gas containing silicon is introduced into a high-temperature furnace, and the pre-lithiated porous carbon and the gas containing silicon are calcined at high temperature, so that nano-silicon particles are deposited in the pores of the porous carbon to obtain composite particles;
[0016] The composite particles are subjected to surface coating treatment to obtain a pre-lithiation silicon-carbon negative electrode material.
[0017] Preferably, the lithium-containing compound includes: one or more of lithium carbonate, lithium borohydride, lithium amide, lithium hydride, and lithium hydroxide;
[0018] The protective atmosphere includes nitrogen atmosphere and / or argon atmosphere;
[0019] The silicon-containing gas includes one or more of monosilane, disilane, tetrafluorosilane and chlorosilane.
[0020] Preferably, the method of mixing the lithium-containing compound and the porous carbon uniformly includes a solid phase mixing method or a liquid phase mixing method;
[0021] The specific process of the solid phase mixing method is: placing the lithium-containing compound and the porous carbon in a mixing device and mixing them evenly;
[0022] The specific process of the liquid phase mixing method is: the lithium-containing compound and the porous carbon powder are uniformly dispersed in an organic solvent, and then placed in a mixing device to mix uniformly; the organic solvent includes: one or more of dimethylformamide, tetrahydrofuran, chloroform, and dimethyl sulfoxide;
[0023] The mixing equipment is any one of a ball mill, a high-speed mixer and an ultrasonic disperser.
[0024] Preferably, the heat treatment conditions are: heating to 300°C-2000°C at a heating rate of 3°C / min-5°C / min, and keeping the temperature for 30min-24h;
[0025] The conditions for high temperature calcination are: heating to 300°C-2500°C at a heating rate of 3°C / min-5°C / min, and keeping the temperature for 30min-12 hours.
[0026] Preferably, the surface coating method includes: one of gas phase coating, liquid phase coating or solid phase coating;
[0027] The liquid-phase coated or solid-phase coated material includes one or more of glucose, sucrose, liquid asphalt, phenolic resin, polyvinylidene fluoride, citric acid, polyvinyl alcohol, polyethylene oxide PEO, polyacrylonitrile PAN, polyvinylidene fluoride PVDF, polymethyl methacrylate PMMA, polypropylene oxide PPO, polyvinylidene chloride PVDC, lithium aluminum titanium phosphate LATP, aluminum chloride hexahydrate, aluminum nitrate, and aluminum acetate;
[0028] The gas-phase coated material includes: one or more of methane, ethylene, propylene, acetylene, and natural gas;
[0029] The temperature range of the surface coating is between 500°C and 1000°C, and the insulation time is between 30min and 16 hours;
[0030] The mass of the surface coating layer accounts for 1%-15% of the total mass of the pre-lithiation silicon-carbon negative electrode material.
[0031] In a third aspect, an embodiment of the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the pre-lithiation silicon-carbon negative electrode material described in the first aspect.
[0032] In a fourth aspect, an embodiment of the present invention provides a lithium battery, wherein the lithium battery comprises the negative electrode plate described in the third aspect.
[0033] The embodiment of the present invention provides a pre-lithiated silicon-carbon negative electrode material and a preparation method and application thereof, wherein pre-lithiated porous carbon is obtained by pre-depositing lithium metal particles in the pores of the porous carbon, and then depositing silicon particles in the pores, wherein the porous carbon has high strength and high hardness, and can effectively improve the volume expansion of silicon-containing particles during the charging and discharging process; and pre-lithiating the porous carbon in advance can, on the one hand, enable the material to quickly replenish lithium ions during the cycle process and improve the first-cycle coulomb efficiency of the material; on the other hand, compared with the situation where lithium and silicon are deposited at the same time, pre-lithiating first can increase the uniformity of silicon deposition, thereby making the electrochemical properties of the material more stable.
[0034] The method for preparing the pre-lithiation silicon-carbon negative electrode material provided by the embodiment of the present invention is simple to operate, low in cost, and can be applied to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.
[0036] Figure 1 It is a flow chart of the preparation method of the pre-lithiation silicon-carbon negative electrode material provided in an embodiment of the present invention.
[0037] Figure 2 This is a scanning electron microscope image (SEM) and a corresponding EDS energy spectrum image of the pre-lithiation silicon-carbon negative electrode material provided in Example 1 of the present invention.
[0038] Figure 3 It is the SEM and corresponding EDS spectrum diagram of the negative electrode material provided in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0039] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0040] The embodiment of the present invention provides a pre-lithiation silicon-carbon negative electrode material, comprising: a composite particle, and a surface coating layer coated on the outer surface of the composite particle; the particle size D of the pre-lithiation silicon-carbon negative electrode material is 50 The particle size is between 1 nm and 80 μm; the mass of the composite particles accounts for 85% to 99% of the total mass of the pre-lithiation silicon-carbon negative electrode material; the mass of the surface coating layer accounts for 1% to 15% of the total mass of the pre-lithiation silicon-carbon negative electrode material.
[0041] Among them, the composite particles are a composite of pre-lithiated porous carbon and nano-silicon particles; the composite particles are obtained by uniformly depositing nano-silicon particles in the pores of pre-lithiated porous carbon; the mass of the pre-lithiated porous carbon accounts for 15%-95% of the total mass of the composite particles; the mass of the nano-silicon particles accounts for 5%-75% of the total mass of the pre-lithiated silicon-carbon negative electrode material.
[0042] The pre-lithiation porous carbon includes lithium metal particles and porous carbon, wherein the lithium metal particles are attached to the surface of the pores of the porous carbon; the pore size of the porous carbon is between 0.1nm-300nm, and the porosity of the porous carbon is between 30%-95%; the mass of the lithium metal particles accounts for 0.1%-10% of the total mass of the pre-lithiation silicon-carbon negative electrode material.
[0043] The present invention provides a method for preparing the above-mentioned pre-lithiation silicon-carbon negative electrode material. Figure 1 As shown, the specific steps include:
[0044] Step 110, fully mixing the lithium-containing compound and the porous carbon to obtain a mixed material, and then placing the mixed material in a high-temperature furnace under a protective atmosphere for heat treatment to vaporize the mixed material, and after deposition, obtain a pre-lithiated porous carbon with lithium metal particles attached to the pore surface of the porous carbon;
[0045] Wherein, the protective atmosphere includes nitrogen atmosphere and / or argon atmosphere;
[0046] The lithium-containing compound includes one or more of lithium carbonate, lithium borohydride, lithium amide, lithium hydride, and lithium hydroxide;
[0047] The method of fully mixing the lithium-containing compound and the porous carbon includes a solid phase mixing method or a liquid phase mixing method; the specific process of the solid phase mixing method is: placing the lithium-containing compound and the porous carbon in a mixing device and mixing them evenly; the specific process of the liquid phase mixing method is: uniformly dispersing the lithium-containing compound and the porous carbon powder in an organic solvent, and then placing them in a mixing device and mixing them evenly; the organic solvent includes: one or more of dimethylformamide, tetrahydrofuran, chloroform, and dimethyl sulfoxide.
[0048] The mixing equipment is any one of ball mill, high-speed mixer and ultrasonic disperser;
[0049] The heat treatment conditions are: heating to 300°C-2000°C at a heating rate of 3°C / min-5°C / min, and keeping the temperature for 30min-24h.
[0050] Step 120, under a protective atmosphere, introducing a gas containing silicon into a high temperature furnace, calcining the pre-lithiated porous carbon and the gas containing silicon at a high temperature, so that nano-silicon particles are deposited in the pores of the porous carbon to obtain composite particles;
[0051] Wherein, the protective atmosphere in this step also includes nitrogen atmosphere and / or argon atmosphere;
[0052] Method for introducing silicon-containing gas into the high-temperature furnace: the silicon-containing gas can be introduced directly at a flow rate of 1L / min-10L / min, or the silicon-containing gas can be introduced into the high-temperature furnace through a carrier gas; the carrier gas is nitrogen or argon, and the flow rate is 1L / min-10L / min;
[0053] The gas containing silicon element includes: one or more of monosilane, disilane, tetrafluorosilane, and chlorosilane;
[0054] The conditions for high-temperature calcination are: heating to 300°C-2500°C at a heating rate of 3°C / min-5°C / min, and keeping the temperature for 30min-12 hours.
[0055] Step 130, performing surface coating treatment on the composite particles to obtain a pre-lithiation silicon-carbon negative electrode material;
[0056] Wherein, the surface coating method includes: one of gas phase coating, liquid phase coating or solid phase coating;
[0057] The materials for liquid phase coating or solid phase coating include: one or more of glucose, sucrose, liquid asphalt, phenolic resin, polyvinylidene fluoride, citric acid, polyvinyl alcohol, polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polypropylene oxide (PPO), polyvinylidene chloride (PVDC), lithium aluminum titanium phosphate LATP, aluminum chloride hexahydrate, aluminum nitrate, and aluminum acetate; the materials for gas phase coating include: one or more of methane, ethylene, propylene, acetylene, and natural gas; the temperature range of surface coating is between 500°C and 1000°C, and the insulation time is between 30min and 16 hours; the mass of the surface coating layer accounts for 1% to 15% of the total mass of the pre-lithiation silicon-carbon negative electrode material.
[0058] The high-temperature furnace used in the preparation method of the present invention is not particularly limited, and may include but is not limited to any one of a tubular furnace, a box furnace, a vacuum furnace, and a vacuum vapor deposition furnace, as long as it can meet the preparation of the above-mentioned pre-lithiation silicon-carbon negative electrode material.
[0059] The pre-lithiation silicon-carbon negative electrode material prepared above in the present invention can be used as an active material or additive material of the negative electrode material for the preparation of the negative electrode plate of a lithium battery. The negative electrode plate of the present application also includes a negative electrode current collector. The present application has no special restrictions on the negative electrode current collector, as long as it can achieve the purpose of the present application, for example, it can include but is not limited to copper foil, copper alloy foil, nickel foil, stainless steel foil or composite current collector, etc.
[0060] The lithium battery assembled using the negative electrode sheet containing the pre-lithiated silicon-carbon negative electrode material of the present invention may include but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.
[0061] The lithium battery prepared by using the pre-lithiation silicon-carbon negative electrode material provided by the embodiment of the present invention has a low volume expansion rate, a high mass specific capacity, good conductivity and cycle life.
[0062] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the pre-lithiation silicon-carbon negative electrode material of the present invention are respectively described below with multiple specific examples.
[0063] Example 1
[0064] This embodiment provides a preparation process and performance test of a pre-lithiation silicon-carbon negative electrode material. The specific preparation process is as follows.
[0065] (1) At room temperature, 0.5 kg of lithium carbonate and 5 kg of porous carbon are placed in an ultrasonic disperser and mixed evenly to obtain a mixed material. The mixed material is then placed in a high-temperature furnace under a nitrogen atmosphere, the pressure is set to 30 MPa, and the temperature is increased to 1000° C. at a heating rate of 5° C. / min to vaporize the mixed material. The mixture is kept warm for 12 hours, cooled and deposited to obtain pre-lithiated porous carbon with lithium metal particles attached to the pore surface of the porous carbon.
[0066] (2) After the high-temperature furnace is cooled to room temperature, nitrogen is introduced into the No. 1 air inlet of the high-temperature furnace as a protective atmosphere, and at the same time, monosilane is introduced into the No. 2 air inlet of the high-temperature furnace at a flow rate of 1 L / min for 3 minutes, and the temperature is increased to 1700°C at a heating rate of 5°C / min and kept at this temperature for 3 hours to deposit nano-silicon particles in the pores of the porous carbon to obtain composite particles.
[0067] (3) The high-temperature furnace is heated to 850° C. in a nitrogen atmosphere, and argon and acetylene gases are introduced at a volume ratio of 1:1 to perform surface carbon coating on the composite particles. After keeping the temperature for 4 hours, the organic gas source is turned off, and the material is discharged and classified after cooling to room temperature to obtain a pre-lithiation silicon-carbon negative electrode material containing a carbon coating layer.
[0068] The SEM and EDS images of the pre-lithiation silicon-carbon negative electrode material prepared in Example 1 are as follows: Figure 2 As shown, according to the particle cross-section micromorphology and EDS elemental analysis, it can be seen that the deposited silicon particles are uniformly distributed in the pores of the porous carbon matrix after pre-lithiation treatment (uniform particle cross-section).
[0069] The pre-lithiation silicon-carbon negative electrode material prepared in this embodiment was used to prepare a negative electrode plate and assemble a button-type half-cell for testing. The specific process is as follows.
[0070] The preparation method of the button half-cell is as follows: the pre-lithiation silicon-carbon negative electrode material, the conductive additive carbon black, and the adhesive (sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:1) are weighed according to a mass ratio of 92%:3%:5%, and the slurry is prepared with a beater, and then coated, dried, and cut into pieces, and assembled into a button half-cell in a glove box.
[0071] The prepared button half-cell was tested in constant current charge and discharge mode using a charge and discharge instrument. The test method is as follows: the discharge and lithium insertion process is a step discharge mode: 1C discharge to 5.0mV, 0.5C discharge to 5.0mV, 0.2C discharge to 5.0mV, 0.1C discharge to 5.0mV; charging and lithium removal: 1C charge to 2V. The first cycle coulomb efficiency data of the tested button half-cell is shown in Table 1.
[0072] Example 2
[0073] This embodiment provides a preparation process and performance test of a pre-lithiation silicon-carbon negative electrode material. The specific preparation process is as follows.
[0074] (1) At room temperature, 0.14 kg of lithium borohydride and 3.5 kg of porous carbon are placed in a high-speed mixer and mixed evenly to obtain a mixed material. The mixed material is then placed in a high-temperature furnace under an argon atmosphere, the pressure is set to 30 MPa, and the temperature is increased to 1000° C. at a heating rate of 5° C. / min to vaporize the mixed material. The mixture is kept warm for 6 hours, and after cooling and deposition, a pre-lithiated porous carbon with lithium metal particles attached to the pore surface of the porous carbon is obtained.
[0075] (2) After the high-temperature furnace is cooled to room temperature, argon gas is introduced into the No. 1 gas inlet of the high-temperature furnace as a protective atmosphere, and disilane gas is introduced into the No. 2 gas inlet of the high-temperature furnace at a flow rate of 2 L / min for 4 minutes, and the temperature is increased to 1100°C at a heating rate of 5°C / min and kept at this temperature for 6 hours, so that nano-silicon particles are deposited in the pores of the porous carbon to obtain composite particles.
[0076] (3) LATP and pre-lithiated porous carbon were dry-sprayed at a mass ratio of 1:150, and the high-temperature furnace was heated to 650°C in an argon atmosphere and kept warm for 3 hours to coat the composite particles with a solid electrolyte. After cooling to room temperature, the materials were discharged and graded to obtain a pre-lithiated silicon-carbon negative electrode material containing a LATP coating layer.
[0077] The pre-lithiation silicon-carbon negative electrode material prepared in this embodiment is used to prepare the negative electrode plate and assemble the button half-cell for testing. The battery assembly and testing methods are the same as those in Example 1. The first cycle coulombic efficiency data of the tested button half-cell are shown in Table 1.
[0078] Example 3
[0079] This embodiment provides a preparation process and performance test of a pre-lithiation silicon-carbon negative electrode material. The specific preparation process is as follows.
[0080] (1) At room temperature, 0.35 kg of lithium amide and 5 kg of porous carbon are placed in an ultrasonic disperser and mixed evenly to obtain a mixed material. The mixed material is then placed in a high-temperature furnace under a nitrogen atmosphere, the pressure is set to 30 MPa, and the temperature is increased to 2000° C. at a heating rate of 5° C. / min to vaporize the mixed material. The mixture is kept warm for 30 minutes, and after cooling and deposition, a pre-lithiated porous carbon with lithium metal particles attached to the pore surface of the porous carbon is obtained.
[0081] (2) After the high-temperature furnace is cooled to room temperature, nitrogen gas is introduced into the No. 1 gas inlet of the high-temperature furnace as a protective atmosphere, and tetrafluorosilane gas is introduced into the No. 2 gas inlet of the high-temperature furnace at a flow rate of 2 L / min for 10 minutes, and the temperature is increased to 2500°C at a heating rate of 5°C / min and kept at this temperature for 30 minutes, so that nano-silicon particles are deposited in the pores of the porous carbon to obtain composite particles.
[0082] (3) 4.5 kg of the composite particles were dispersed in 1 mol / L ammonium formate buffer solution, ultrasonicated for 30 min to make them evenly dispersed, 0.1 kg of aluminum sulfate powder was added, and then the mixed solution was fully reacted in a reactor at 100 ° C for 2 hours, washed to neutrality and vacuum dried for 12 hours to obtain a pre-lithiation silicon-carbon negative electrode material containing an aluminum oxide coating layer.
[0083] The pre-lithiation silicon-carbon negative electrode material prepared in this embodiment is used to prepare the negative electrode plate and assemble the button half-cell for testing. The battery assembly and testing methods are the same as those in Example 1. The first cycle coulombic efficiency data of the tested button half-cell are shown in Table 1.
[0084] Example 4
[0085] This embodiment provides a preparation process and performance test of a pre-lithiation silicon-carbon negative electrode material. The specific preparation process is as follows.
[0086] (1) At room temperature, a mixture of 0.035 kg of lithium carbonate and lithium amide (mass ratio of 1:1) and 3.5 kg of lithium amine are placed in an ultrasonic disperser and mixed evenly to obtain a mixed material. The mixed material is then placed in a high-temperature furnace under a nitrogen atmosphere, heated to 300° C. at a heating rate of 3° C. / min under normal pressure, and kept warm for 24 hours. After cooling, a pre-lithiated porous carbon with lithium metal particles attached to the pore surface of the porous carbon is obtained.
[0087] (2) After the high-temperature furnace is cooled to room temperature, nitrogen is introduced into the No. 1 air inlet of the high-temperature furnace as a protective atmosphere, and chlorosilane is introduced into the No. 2 air inlet of the high-temperature furnace at a flow rate of 1 L / min for 4 minutes, and the temperature is increased to 300°C at a heating rate of 3°C / min and kept at this temperature for 12 hours to deposit nano-silicon particles in the pores of the porous carbon to obtain composite particles.
[0088] (3) The high-temperature furnace was heated to 700° C. in a nitrogen atmosphere, and argon and ethylene gases were introduced at a volume ratio of 1:1.5 to perform surface carbon coating on the composite particles. After keeping the temperature for 3 hours, the organic gas source was turned off, and the material was discharged and classified after cooling to room temperature to obtain a pre-lithiation silicon-carbon negative electrode material containing a carbon coating layer.
[0089] The pre-lithiation silicon-carbon negative electrode material prepared in this embodiment is used to prepare the negative electrode plate and assemble the button half-cell for testing. The battery assembly and testing methods are the same as those in Example 1. The first cycle coulombic efficiency data of the tested button half-cell are shown in Table 1.
[0090] Example 5
[0091] This embodiment provides a preparation process and performance test of a pre-lithiation silicon-carbon negative electrode material. The specific preparation process is as follows.
[0092] (1) At room temperature, a mixture of 0.5 kg of lithium carbonate and lithium borohydride (mass ratio of 1:1) and 5 kg of porous carbon are uniformly dispersed in 8 L of dimethylformamide to obtain a mixed slurry. The mixed slurry is then placed in a high-temperature furnace under a nitrogen atmosphere and heated to 500°C at a heating rate of 5°C / min to vaporize the mixed slurry. The mixed slurry is then calcined at 1000°C for 12 hours. After cooling and deposition, a pre-lithiated porous carbon with lithium metal particles attached to the pore surface of the porous carbon is obtained.
[0093] (2) After the high-temperature furnace is cooled to room temperature, argon gas is introduced into the No. 1 air inlet of the high-temperature furnace as a protective atmosphere, and chlorosilane is introduced into the No. 2 air inlet of the high-temperature furnace at a flow rate of 3 L / min for 4 minutes, and the temperature is increased to 300°C at a heating rate of 5°C / min and kept at this temperature for 12 hours to deposit nano-silicon particles in the pores of the porous carbon to obtain composite particles.
[0094] (3) The high-temperature furnace is heated to 850° C. in a nitrogen atmosphere, and argon and natural gas are introduced at a volume ratio of 1:1.5 to perform surface carbon coating on the composite particles. After keeping the temperature for 4 hours, the organic gas source is turned off, and the material is discharged and classified after cooling to room temperature to obtain a pre-lithiation silicon-carbon negative electrode material containing a carbon coating layer.
[0095] The pre-lithiation silicon-carbon negative electrode material prepared in this embodiment is used to prepare the negative electrode plate and assemble the button half-cell for testing. The battery assembly and testing methods are the same as those in Example 1. The first cycle coulombic efficiency data of the tested button half-cell are shown in Table 1.
[0096] Example 6
[0097] This embodiment provides a preparation process and performance test of a pre-lithiation silicon-carbon negative electrode material. The specific preparation process is as follows.
[0098] (1) At room temperature, a mixture of 0.14 kg of lithium borohydride and lithium amide (mass ratio of 1:1) and 5 kg of porous carbon are uniformly dispersed in 6 L of tetrahydrofuran to obtain a mixed slurry, and then the mixed slurry is placed in a high-temperature furnace under an argon atmosphere, and the temperature is increased to 500°C at a heating rate of 5°C / min to vaporize the mixed slurry, and then calcined at 1500°C for 6 hours. After cooling and deposition, a pre-lithiated porous carbon with lithium metal particles attached to the pore surface of the porous carbon is obtained.
[0099] (2) After the high-temperature furnace is cooled to room temperature, nitrogen gas is introduced into the No. 1 gas inlet of the high-temperature furnace as a protective atmosphere, and tetrafluorosilane gas is introduced into the No. 2 gas inlet of the high-temperature furnace at a flow rate of 3 L / min for 10 minutes, and the temperature is increased to 2500°C at a heating rate of 5°C / min and kept at this temperature for 6 hours, so that nano-silicon particles are deposited in the pores of the porous carbon to obtain composite particles.
[0100] (3) The high-temperature furnace is heated to 650° C. in a nitrogen atmosphere, and argon and natural gas are introduced at a volume ratio of 1:1.5 to perform surface carbon coating on the composite particles. After keeping the temperature for 3 hours, the organic gas source is turned off, and the material is discharged and classified after cooling to room temperature to obtain a pre-lithiation silicon-carbon negative electrode material containing a carbon coating layer.
[0101] The pre-lithiation silicon-carbon negative electrode material prepared in this embodiment is used to prepare the negative electrode plate and assemble the button half-cell for testing. The battery assembly and testing methods are the same as those in Example 1. The first cycle coulombic efficiency data of the tested button half-cell are shown in Table 1.
[0102] Example 7
[0103] This embodiment provides a preparation process and performance test of a pre-lithiation silicon-carbon negative electrode material. The specific preparation process is as follows.
[0104] (1) At room temperature, 0.35 kg of lithium hydride and 5 kg of porous carbon are uniformly dispersed in 8 L of chloroform to obtain a mixed slurry. The mixed slurry is then placed in a high-temperature furnace under a nitrogen atmosphere and heated to 500°C at a heating rate of 5°C / min to vaporize the mixed slurry. The mixed slurry is kept warm for 6 hours. After cooling and deposition, a pre-lithiated porous carbon with lithium metal particles attached to the pore surface of the porous carbon is obtained.
[0105] (2) After the high-temperature furnace is cooled to room temperature, nitrogen is introduced into the No. 1 air inlet of the high-temperature furnace as a protective atmosphere, and disilane is introduced into the No. 2 air inlet of the high-temperature furnace at a flow rate of 5 L / min for 4 minutes, and the temperature is increased to 1100°C at a heating rate of 5°C / min and kept at this temperature for 6 hours, so that nano-silicon particles are deposited in the pores of the porous carbon to obtain composite particles.
[0106] (3) The high temperature furnace was heated to 1000° C. in a nitrogen atmosphere, and argon and methane gases were introduced at a volume ratio of 1:1 to perform surface carbon coating on the composite particles. After keeping the temperature for 4 hours, the organic gas source was turned off, and the material was discharged and classified after cooling to room temperature to obtain a pre-lithiation silicon-carbon negative electrode material containing a carbon coating layer.
[0107] The pre-lithiation silicon-carbon negative electrode material prepared in this embodiment is used to prepare the negative electrode plate and assemble the button half-cell for testing. The battery assembly and testing methods are the same as those in Example 1. The first cycle coulombic efficiency data of the tested button half-cell are shown in Table 1.
[0108] Example 8
[0109] This embodiment provides a preparation process and performance test of a pre-lithiation silicon-carbon negative electrode material. The specific preparation process is as follows.
[0110] (1) At room temperature, a mixture of 0.035 kg of lithium hydroxide and lithium amide (mass ratio of 1:1) and 5 kg of porous carbon are uniformly dispersed in 6 L of dimethyl sulfoxide to obtain a mixed slurry. The mixed slurry is then placed in a high-temperature furnace under an argon atmosphere and heated to 500°C at a heating rate of 5°C / min to vaporize the mixed slurry. The mixed slurry is then calcined at 300°C for 24 hours. After cooling and deposition, a pre-lithiated porous carbon with lithium metal particles attached to the pore surface of the porous carbon is obtained.
[0111] (2) After the high-temperature furnace is cooled to room temperature, nitrogen is introduced into the No. 1 air inlet of the high-temperature furnace as a protective atmosphere, and monosilane is introduced into the No. 2 air inlet of the high-temperature furnace at a flow rate of 3 L / min for 3 min. The temperature is then increased to 1700°C at a heating rate of 5°C / min and maintained for 3 hours to deposit nano-silicon particles in the pores of the porous carbon to obtain composite particles.
[0112] (3) The high-temperature furnace was heated to 700° C. in a nitrogen atmosphere, and argon and methane gases were introduced at a volume ratio of 1:1.5 to perform surface carbon coating on the composite particles. After keeping the temperature for 3 hours, the organic gas source was turned off, and the material was discharged and classified after cooling to room temperature to obtain a pre-lithiation silicon-carbon negative electrode material containing a carbon coating layer.
[0113] The pre-lithiation silicon-carbon negative electrode material prepared in this embodiment is used to prepare the negative electrode plate and assemble the button half-cell for testing. The battery assembly and testing methods are the same as those in Example 1. The first cycle coulombic efficiency data of the tested button half-cell are shown in Table 1.
[0114] In order to better illustrate the effects of the embodiments of the present invention, comparative examples 1-2 are compared with the above embodiments.
[0115] Comparative Example 1
[0116] This comparative example provides a preparation of a negative electrode material, which is different from Example 1 in that the porous carbon is not pre-lithiated, and the other preparation processes are the same as those of Example 1.
[0117] The negative electrode material prepared in this comparative example was used to prepare negative electrode plates and assembled into button-type half-cells for testing. The battery assembly and testing methods were the same as those in Example 1. The first-cycle coulomb efficiency data of the tested button-type half-cells are detailed in Table 1.
[0118] Comparative Example 2
[0119] This comparative example provides a preparation of a negative electrode material, which is different from Example 2 in that the porous carbon is not pre-lithiated, and the other preparation processes are the same as those in Example 2.
[0120] The negative electrode material prepared in this comparative example was used to prepare negative electrode plates and assembled into button-type half-cells for testing. The battery assembly and testing methods were the same as those in Example 1. The first-cycle coulomb efficiency data of the tested button-type half-cells are detailed in Table 1.
[0121] Comparative Example 3
[0122] This comparative example provides a preparation method of a negative electrode material, which is different from Example 1 in that the porous carbon is not pre-lithiated in advance, but the gas containing lithium element and the gas containing silicon element are deposited in the pores of the porous carbon at the same time.
[0123] The SEM image of the negative electrode material prepared in this comparative example is as follows: Figure 3 As shown, it can be seen that in the microscopic cross-section of the particles in which the lithium-containing gas and the silicon-containing gas are simultaneously deposited in the pores of the porous carbon, the silicon particles are unevenly distributed (uneven particle cross-section).
[0124] The negative electrode material prepared in this comparative example was used to prepare negative electrode plates and assembled into button-type half-cells for testing. The battery assembly and testing methods were the same as those in Example 1. The first-cycle coulomb efficiency data of the tested button-type half-cells are detailed in Table 1.
[0125] Table 1 is a summary of the first cycle coulombic efficiency test data of button-type half-cells assembled in Examples 1-8 and Comparative Examples 1-2:
[0126]
[0127]
[0128] By comparing the test data in Table 1, it can be seen that the first-cycle coulomb efficiency of the battery assembled by preparing the negative electrode plates using pre-lithiated silicon-carbon negative electrode materials in Examples 1-8 of the present invention is higher than that of Comparative Examples 1-2, especially the first-cycle coulomb efficiency of Examples 1-2 is improved by about 3% relative to that of Comparative Examples 1-2, indicating that the pre-lithiated silicon-carbon negative electrode material proposed in the present invention can effectively improve the disadvantage of low first-cycle coulomb efficiency of traditional silicon-carbon negative electrode materials. This is because the pre-lithiated silicon-carbon negative electrode material prepared by the present invention is obtained by pre-depositing lithium metal particles in the pores of porous carbon to obtain pre-lithiated porous carbon, and then depositing silicon particles in the pores, wherein the porous carbon has high strength and high hardness, and can effectively improve the volume expansion of silicon-containing particles during charging and discharging; and pre-lithiating the porous carbon in advance can, on the one hand, enable the material to quickly replenish lithium ions during the cycle and improve the first-cycle coulomb efficiency of the material, and on the other hand, compared with the case where lithium and silicon are deposited at the same time, pre-lithiating first can increase the uniformity of silicon deposition, thereby making the electrochemical performance of the material more stable.
[0129] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A pre-lithiation silicon-carbon negative electrode material, characterized in that: The pre-lithiation silicon-carbon negative electrode material comprises: a composite particle, and a surface coating layer coated on the outer surface of the composite particle; The mass of the composite particles accounts for 85%-99% of the total mass of the pre-lithiation silicon-carbon negative electrode material; The composite particles are composites of pre-lithiated porous carbon and nano-silicon particles; the composite particles are obtained by uniformly depositing nano-silicon particles in the pores of the pre-lithiated porous carbon; the mass of the pre-lithiated porous carbon accounts for 15%-95% of the total mass of the composite particles; The pre-lithiation porous carbon comprises lithium metal particles and porous carbon, wherein the lithium metal particles are attached to the surface of the pores of the porous carbon; the mass of the lithium metal particles accounts for 0.1%-10% of the total mass of the pre-lithiation silicon-carbon negative electrode material.
2. The pre-lithiation silicon-carbon negative electrode material according to claim 1, characterized in that: The mass of the surface coating layer accounts for 1%-15% of the total mass of the pre-lithiation silicon-carbon negative electrode material; The mass of the nano silicon particles accounts for 5%-75% of the total mass of the pre-lithiation silicon-carbon negative electrode material.
3. The pre-lithiation silicon-carbon negative electrode material according to claim 1, characterized in that: The particle size D of the pre-lithiation silicon-carbon negative electrode material 50 The diameter of the porous carbon pores is between 1nm and 80μm; the pore size of the porous carbon pores is between 0.1nm and 300nm; the porosity of the porous carbon is between 30% and 95%.
4. A method for preparing the pre-lithiation silicon-carbon negative electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: The lithium-containing compound and the porous carbon are fully mixed to obtain a mixed material, and then the mixed material is placed in a high-temperature furnace for heat treatment under a protective atmosphere to vaporize the mixed material, and after deposition, a pre-lithiated porous carbon with lithium metal particles attached to the pore surface of the porous carbon is obtained; In a protective atmosphere, a gas containing silicon is introduced into a high-temperature furnace, and the pre-lithiated porous carbon and the gas containing silicon are calcined at high temperature, so that nano-silicon particles are deposited in the pores of the porous carbon to obtain composite particles; The composite particles are subjected to surface coating treatment to obtain a pre-lithiation silicon-carbon negative electrode material.
5. The preparation method according to claim 4, characterized in that: The lithium-containing compound includes: one or more of lithium carbonate, lithium borohydride, lithium amide, lithium hydride, and lithium hydroxide; The protective atmosphere includes nitrogen atmosphere and / or argon atmosphere; The silicon-containing gas includes one or more of monosilane, disilane, tetrafluorosilane and chlorosilane.
6. The preparation method according to claim 4, characterized in that: The method of fully and uniformly mixing the lithium-containing compound and the porous carbon includes a solid phase mixing method or a liquid phase mixing method; The specific process of the solid phase mixing method is: placing the lithium-containing compound and the porous carbon in a mixing device and mixing them evenly; The specific process of the liquid phase mixing method is: the lithium-containing compound and the porous carbon powder are uniformly dispersed in an organic solvent, and then placed in a mixing device to mix uniformly; the organic solvent includes: one or more of dimethylformamide, tetrahydrofuran, chloroform, and dimethyl sulfoxide; The mixing equipment is any one of a ball mill, a high-speed mixer and an ultrasonic disperser.
7. The preparation method according to claim 4, characterized in that: The heat treatment conditions are: heating to 300°C-2000°C at a heating rate of 3°C / min-5°C / min, and keeping the temperature for 30min-24 hours; The conditions for high temperature calcination are: heating to 300°C-2500°C at a heating rate of 3°C / min-5°C / min, and keeping the temperature for 30min-12 hours.
8. The preparation method according to claim 4, characterized in that: The surface coating method includes: one of gas phase coating, liquid phase coating or solid phase coating; The liquid-phase coated or solid-phase coated material includes one or more of glucose, sucrose, liquid asphalt, phenolic resin, polyvinylidene fluoride, citric acid, polyvinyl alcohol, polyethylene oxide PEO, polyacrylonitrile PAN, polyvinylidene fluoride PVDF, polymethyl methacrylate PMMA, polypropylene oxide PPO, polyvinylidene chloride PVDC, lithium aluminum titanium phosphate LATP, aluminum chloride hexahydrate, aluminum nitrate, and aluminum acetate; The gas-phase coated material includes: one or more of methane, ethylene, propylene, acetylene, and natural gas; The temperature range of the surface coating is between 500°C and 1000°C, and the insulation time is between 30min and 16 hours; The mass of the surface coating layer accounts for 1%-15% of the total mass of the pre-lithiation silicon-carbon negative electrode material.
9. A negative electrode plate, characterized in that: The negative electrode plate comprises the pre-lithiation silicon-carbon negative electrode material as described in any one of claims 1 to 3 above.
10. A lithium battery, characterized in that: The lithium battery comprises the negative electrode sheet as described in claim 9 above.
Citation Information
Cited By
Negative pole piece, battery and electric device
CN118073520A
Spherical porous carbon as well as preparation method and application thereof
CN119976806A
Active material and preparation method thereof, electrode and secondary battery
CN120473490A
Pre-lithiated silicon-carbon negative electrode, negative electrode plate, secondary battery and preparation method of pre-lithiated silicon-carbon negative electrode
CN120497302A
A pre-lithiated silicon-carbon negative electrode, negative electrode sheet, secondary battery and preparation method thereof
CN120497302B